Social Facebook With Big Six Approaches for Improved Students’ Learning Performance and Behavior: A Case Study of a Project Innovation and Implementation Course - Su, Yu-Sheng; Chen, Hong-Ren (Frontiers in Psychology, 2020)
In Taiwan, traditional classroom lectures are gradually developing into diversifying digital learning. The traditional classroom learning environment gradually changes into the social network websites, and Facebook has been commonly applied to classroom lectures so as to provide a space for sharing and discussing learning materials and knowledge for teacher and students. In this paper, we focus on the effects of applying Big Six approaches to Facebook on students' learning performance and learning behavior in the project innovation and implementation course. The participants are 72 freshmen in a college located in the north of Taiwan. The experimental participants who take the course are divided into two class as the experimental group and the control group. The experimental group uses Facebook combining with Big Six approaches. The control group uses the traditional classroom tools combining with Big Six approaches. The experimental results show that the learning performance and creativity development of the students from the experimental group enhances after using Facebook blending with Big Six methods, which means that there is a great social interaction and discussion cycle. On the other hand, students from the control group are only guided by the teacher. On account of the lack of interactions from Internet and social learning community, there is not an obvious enhancement in students' learning performance and creative development. By learning behavior analysis, we found that the teacher practices the tips for guiding experimental students to solve the encountered problem, and then the students reply to the classmate's questions.